Genotype specific pathogenicity of hepatitis E virus at the human maternal-fetal interface. Issue 1 (December 2018) - Gouilly, Jordi; Chen, Qian; Siewiera, Johan; Cartron, Géraldine; Levy, Claude; Dubois, Martine; Al-Daccak, Reem; Izopet, Jacques; Jabrane-Ferrat, Nabila; El Costa, Hicham
Abstract Hepatitis E virus (HEV) infection, particularly HEV genotype 1 (HEV-1), can result in fulminant hepatic failure and severe placental diseases, but mechanisms underlying genotype-specific pathogenicity are unclear and appropriate models are lacking. Here, we model HEV-1 infection ex vivo at the maternal-fetal interface using thedecidua basalis and fetal placenta, and compare its effects to the less-pathogenic genotype 3 (HEV-3). We demonstrate that HEV-1 replicates more efficiently than HEV-3 both in tissue explants and stromal cells, produces more infectious progeny virions and causes severe tissue alterations. HEV-1 infection dysregulates the secretion of several soluble factors. These alterations to the cytokine microenvironment correlate with viral load and contribute to the tissue damage. Collectively, this study characterizes an ex vivo model for HEV infection and provides insights into HEV-1 pathogenesis during pregnancy that are linked to high viral replication, alteration of the local secretome and induction of tissue injuries. Hepatitis E virus (HEV) infection can result in severe placental disease, but mechanisms underlying pathogenicity are poorly understood. Here, the authors develop an ex vivo model for HEV infection at the maternal-fetal interface and compare pathogenicity of different HEV genotypes.